PENGARUH KOMITE AUDIT, CORPORATE GOVERNANCE, DAN MANAJEMEN LABA, TERHADAP TAX AVOIDANCE DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2020-2022) - Nova Setya Fernanda; Dul Muid (Diponegoro Journal of Accounting, 2026)
Firm Value is the most important basic learning for investors, therefore it is part of the market indicators which are an assessment of the value of all market prices. Tax is the main income that comes from a country with a very large income. The committee has a minimum of three members, called the audit committee, which is responsible for monitoring the running of a company and monitoring external audits of financial reporting. Corporate governance refers to a set of rules and regulations governing and overseeing the activities of a company. The LQ45 stock index is a stock index that has high capitalization in the stock market, which has high trading intensity, a high company growth work system and has good financial conditions, has not changed and has objects that have been tested on the IDX, and these LQ45 shares have been proven safe by having a good stock value measure, and resulting in low risk.